Pengaruh penerapan model pembelajaran problem based learning (PBL) berbantuan LKS pada materi gaya dan hukum Newton terhadap kompetensi fisika siswa kelas X MAN 1 Kerinci - Putri Nurhaliza; yurnetti -; Festiyed -; letmi dwiridal (PILLAR OF PHYSICS EDUCATION, 2019)
Student physics competency can be achieved by applying the problem based learning (PBL) learning model. The purpose of this study was to determine the differences in the Physics competence of MAN 1 Kerinci students between classes using the Problem Based learning model and those not and to determine the percentage of influence of the application of the Problem Based learning model on the Physics competence of MAN 1 Kerinci students. The population in this study were all students of class X semester 1 in MAN 1 Kerinci who were enrolled in Academic Year (TA) 2018 / 2019. The technique used in sampling was cluster random sampling. The sample used was class X MIPA 1 as an experimental class and X MIPA 2 as a control class. The data in this study are the physics competencies of students after being given treatment including attitude competencies, knowledge and skills. After conducting research and continuing with analyzing the research data it can be concluded that the application of PBL learning models has a significant influence on the achievement of physics competence in class X MAN 1 Kerinci. The application of PBL learning model influences the attainment of attitude competence by 15.52%, the achievement of knowledge competence by 21.12% while the achievement of students' skills competence is 16.75%.